From Disneyization to Netflixification: Algorithms and the Production of Taste - Wojtyna, Miłosz (Zagadnienia Rodzajów Literackich, 2025)
This paper examines the transformation of cultural production and consumption in the 21st century through a comparative analysis of Bryman’s concept of Disneyization and the emergent phenomenon of Netflixification. As digital platforms permeate diverse domains of cultural production and social activity such as education, sport, reading, and eating, a derivative cultural logic unfolds which partly imitates that of Disney’s theme parks, and partly develops from larger trends in algorithmic capitalism based on the production of user subjectivities and taste. Drawing on Horkheimer and Adorno’s critique of the culture industry, the paper argues that Netflixification is both a continuation and an intensification of earlier trends in cultural commodification: it draws from the model Bryman described, and adapts it to the technological conditions of the algorithmic age in order to present the form of pseudo-engagement capitalism generated in audiences to then exploit them through an algorithm-based production of taste. The paper outlines key features of both Disneyization and Netflixification, summarises research to-date on the intersections of culture and algorithms, and develops a refined theoretical framework for understanding the implications of Netflixification within the broader context of digital capitalism.